Dépasser le modèle du musée irénique. L’étude du processus de cocréation d’un dispositif de médiation numérique pour les salles des arts du Tout-Monde au Musée des beaux-arts de Montréal - Delfino, Laura (Muséologies)

(untitled) (Association Québécoise de Promotion des Recherches Étudiantes en Muséologie (AQPREM), 2023)
Examining participatory practises and inclusion projects requires reflecting on the museum as a political space and questioning the power relationships it nourishes. A review of the literature on the idea of the sense of belonging in a wide variety of disciplinary fields led to an awareness of the different dimensions of that feeling and its integration in the political discourse. More specifically, in terms of this article, the feeling of belonging is problematic in the context of art museums, where the concept is often translated to the institution’s benevolent attitude towards racialized groups that have historically been discriminated against and are not in the habit of visiting museums. When these people are invited to collaborate with the museal institution, the co-creation process generally proceeds according to codes established by the institution. This tendency to adopt a charitable position towards the Other, avoiding any sort of tension, is what we call “a irenic museum” (from the Greek εἰρήνη [eirnê] meaning “peace”). By focusing on what unifies rather than on what divides, the irenical approach avoids conflict in order to foster coexistence with one another. By analyzing the process of co-creating a digital mediation system for the Arts of One World galleries at the Montreal Museum of Fine Arts (MMFA), we suggest a critical look at the design thinking approach centred on the human at PRISM, the museum’s Digital Mediation Innovation Lab. Can we move beyond the limits of the peace museum by promoting equal interaction between those involved?